2018
DOI: 10.1177/0735633117751604
|View full text |Cite
|
Sign up to set email alerts
|

Social Media Usage of Students, Role of Tie Strength, and Perceived Task Performance

Abstract: The extensive use of social media has encouraged university teachers to consider employing social media as new e-learning platforms. This study explored the relationship between social media usage and constructive learning performance (perceived group task performance). Specifically, this work focused on the mediating role of communication in group and the moderating role of tie strength in online social networking. Survey data were collected from students in a senior-level business course. Students were asked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 81 publications
(106 reference statements)
0
11
0
Order By: Relevance
“…These features enable many people to easily share their ideas, opinions, experiences, prospects, information, and knowledge freely via SM (Rau et al, 2008;Al-Rahmi et al, 2018). Moreover, SM usage enhances students' communication skills, and this means of communication enables them to collaborate and communicate despite geographical constraints, boosting their learning performance (Williams et al, 2012;Qi, 2019;Berkani, 2020) and encouraging them to work in groups; thus, members help each other by correcting each other's errors, improving their learning progress or performance (Paul et al, 2005). SM provides a platform for students and teachers to discuss their concepts and examine them with their peers (Tess, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…These features enable many people to easily share their ideas, opinions, experiences, prospects, information, and knowledge freely via SM (Rau et al, 2008;Al-Rahmi et al, 2018). Moreover, SM usage enhances students' communication skills, and this means of communication enables them to collaborate and communicate despite geographical constraints, boosting their learning performance (Williams et al, 2012;Qi, 2019;Berkani, 2020) and encouraging them to work in groups; thus, members help each other by correcting each other's errors, improving their learning progress or performance (Paul et al, 2005). SM provides a platform for students and teachers to discuss their concepts and examine them with their peers (Tess, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, from a strategic perspective, research has shown that two-way internal communication will encourage empowerment in terms of freely sharing ideas free and support employee engagement (Karanges et al, 2015 ; Lemon & Palenchar, 2018 ). Furthermore, open communication, effective storytelling, channels, and content targeted at employees’ needs and preferences, as well as communication geared toward establishing a sense of belonging and promoting employees’ voicing actions, have been suggested to boost employee engagement (Ewing et al, 2019 ; Qi, 2019 ; Ruck et al, 2017 ). However, personal social media as a new communication strategy for employees to communicate with their audience, little is known on how this communication strategy and the tie strength of the social media network affect employee engagement; this study seeks to explore this phenomenon and develop a deeper insight into it.…”
Section: Literature Review and Research Frameworkmentioning
confidence: 99%
“…They concluded an increase in student confidence and SoMe being beneficial in knowledge acquisition. SoMe increases cooperative learning, teacher/student communication (Qi, 2019;Bal & Bicen, 2017) and increased motivation in learning (Bal & Bicen, 2017).…”
Section: Introductionmentioning
confidence: 99%